Pengaruh Rasio Keuangan Terhadap Harga Saham Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - Wahyuni EDT, Risa (Universitas Sumatera Barat, 2020)
This study aims to determine the extent of the influence of current ratio, debt to equity ratio and return on assets on the share price of food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. This research is quantitative research. The population of this study are all food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sample selection was carried out using the puposive sampling method and resulted in a selected sample of 10. The data collection technique used is documentation, with documents in the form of company financial reports for 2016-2020. The data analysis technique uses descriptive analysis, classical assumption test, and hypothesis testing using multiple linear analysis with the help of spss 18. The results showed that: Current ratio has no significant effect on stock prices with a significant level of 0.055> 0.05. Debt to equity, has no significant effect on stock prices with a significant level of 0.358> 0.05. And retunt on assets has a significant effect on stock prices with a significant level of 0.013 <0.05. Current ratio, debtto equity ratio and return on assets simultaneously affect stock prices with a significant level of 0.027 <0.05. For the results of the coefficient of determination (R2) of 0.125 or 12.5% which means that the stock price can be influenced by the current ratio, debt to equity ratio, and return on assets by 12.5% while the remaining 87.5% is a variant that is not explained in this study.